Early Language Environments Predict Aspects of Explicit Language Awareness Development. Issue 2 (14th November 2019) - Atagi, Natsuki; Sandhofer, Catherine M.
Abstract: Although language awareness is typically defined as the explicit understanding of language's functions and conventions, much evidence on the influence of diverse language environments on language awareness has shown implicit understandings of language. In contrast, this study examined whether exposure to linguistic diversity predicted monolingual children's explicit language awareness. We examined four aspects of children's explicit language awareness: ability to label languages, understanding of the communicative consequences of speaking different languages, understanding of labeling conventions, and awareness of their language environment. Participants were monolingual 3‐ to 5‐year‐olds ( N = 81) who were from (a) a relatively linguistically homogenous community, (b) a relatively linguistically diverse community, or (c) a bilingual household in a relatively linguistically diverse community. Results suggest that community linguistic diversity and home bilingual exposure predict children's explicit language labeling and understanding of labeling conventions but not other aspects of language awareness. These findings provide insight into the role of early language environments in explicit language awareness development. Abstract :